Correlation between BMI and ADLs with Mental Emotional Disorder among Elderly - Qonitah, Nabilah; Isfandiari, Muhammad Atoillah (Jurnal Berkala Epidemiologi, 2015)
ABSTRACTThe increasing of life expectancy led to a growing number of elderly. There are many thing that occurs caused by aging process, one of them is decreases of body function. Decreasing body function can cause variety of health problems. The problem that may occurs are malnutrition, chronic disease, and lack of independence in performing daily activities. All of them are risk factor of mental emotional disorder. This study was conducted to determined the relationship between mental emotional disorders in the Elderly Care Unit Jombang in Kediri. This research was analytical study and used cross sectional. Dependent variable was mental emotional disorders. Independent variables were BMI, physical independence and characteristic. Interview was conducted to obtain information about variables in this study. Data analyzed by chi square and pearson correlation. The prevalence of mental disorders found in this study was 23,4%. Respondents who didnât have physical independence were 4,3%. Respondents who had body mass index that wasnât normal is 26,2%. The variables showed correlation only variable physical independence and mental emotional disorders (p = 0,008). While the body mass index and characteristic were not showed correlation with mental emotional disorders. The conclusion of this study was the elderly at risk for emotional suffering mental disorders. Physical independence associated with mental disorders in elderly emotional. So the need for more attention especially from the psychological to the elderly who do not have physical independence.Keywords: risk factors, BMI, physical independence, mental emotional Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  disorder, elderly